Inhibition of DNA Topoisomerase I and growth inhibition of human cancer cell lines by an oleanane from Junellia aspera (verbenaceae) - Pungitore, C.R.; Padrón, J.M.; Leon, L.G.; García, C.; Ciuffo, G.M.; Martin, V.S.; Tonn, C.E. (Cellular and Molecular Biology, 2007)
DNA topoisomerases and DNA polymerases are enzymes that play a crucial role in DNA metabolism events such as replication, transcription, recombination, and chromosome segregation during mitosis. Thus, DNA topoisomerases and DNA polymerases inhibitors could be expected to have antitumor effects. Naturally occurring triterpenoids isolated from Junellia aspera (Gillies & Hook; Moldenke) (Verbenaceae) were assayed for human DNA topoisomerase I and Taq DNA polymerase inhibitory activities. Maslinic acid (2) and its diacetyl derivative (7) showed human DNA topoisomerase I inhibitory activity with IC50 values in the range of 76-80 Î¼M and growth inhibition against various human solid tumour cell lines with GI50 values in the range of 5-18 Î¼M. The triterpene frames could be used for screening new inhibitors of the enzyme, and computer-simulated drug design using the frame and pocket structure of enzyme may in theory be a possible approach to develop new inhibitors.